Comparative study of the pesticides and antibiotics residue in duck meat reared in closed house and open house free range system - Mohd Tahar, Nur Syahirah (2015)
This study compares on antibiotics and pesticides residue in commercial Pekin duck meat from closed house and open house free range system. A total of 16 matured ducks using same type of commercial diet with 8 from each different rearing system were subjected to this study. The antibiotic and pesticides residue experiment was conducted using six plate test method, ELISA method and QuEChERS method respectively. Six plate test method for screening of qualitative detection of a group of antibiotics in animal tissue; macrolides, aminoglycosides, tetracyclines, sulfonamides, B-lactam and quinolones shows negative result (<2mm or no annular zone around tissue disc) Meanwhile, ELISA method for banned drugs; Chloramphenicol, Nitrofuran, Beta-agonist show negative for all samples. QuEChERS method using GC-ECD/GC-MS for pesticide residue; also shows the negetif result. Thus, the different rearing method does not contribute to the unnecessary usage of antibiotic; either the duck were affected by the pesticides residue subjected to the ponds in open house free range system.